The Influence Of Service Quality And Company’s Image On Customer Satisfaction At Bank Muamalat Bengkulu - Erenherlika Erenherlika; Neri Susanti; Zoniarti Zoniarti (Penerbit Jurnal Indonesia, 2023)
The aim of this research is to determine the influence of service quality and company’s image on customer satisfaction at Bank Muamalat Bengkulu Branch. The sample in this research was 100 customers who made transactions at Bank Muamalat Bengkulu Branch. The sampling technique is an accidental sampling technique for collecting data using a questionnaire and the analysis method used is multiple linear regression, classical assumption testing and hypothesis testing. Based on the results of multiple linear regression research, it shows that Y=14.005+2.522X1+5.333X2+2.683. The research results show that the variable Service Quality (X1) shows tcount 2.522 > ttable 1.660 and is significant 0.013 < 0.05, so the hypothesis results Ha are accepted and Ho is rejected, meaning that Service Quality (X2) has a positive and significant effect on Customer Satisfaction (Y). The variable Company Image (X2) shows tcount 5.333 > ttable 1.660 and is significant 0.000 < 0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning that Company’s Image (X2) has a positive and significant effect on Customer Satisfaction (Y). The results of simultaneous hypothesis calculations show a significant value of 0.000 < 0.05, meaning that together, X1 (Service Quality) has a positive and significant influence on Customer Satisfaction (Y) and X2 has a positive and significant influence on Customer Satisfaction (Y)